Solidification/stabilization of ASR fly ash using thiomer material: Optimization of compressive strength and heavy metals leaching - Baek, Jin Woong (Animo Repository, 2017)
Optimization studies of a novel and eco-friendly construction material, Thiomer, was investigated in the solidification/stabilization of automobile shredded residue (ASR) fly ash. A D-optimal mixture design was used to evaluate and optimize maximum compressive strength and heavy metals leaching by varying Thiomer (20–40 wt%), ASR fly ash (30–50 wt%) and sand (20–40 wt%). The analysis of variance was utilized to determine the level of significance of each process parameters and interactions. The microstructure of the solidified materials was taken from a field emission-scanning electron microscopy and energy dispersive X-ray spectroscopy that confirmed successful Thiomer solidified ASR fly ash due to reduced pores and gaps in comparison with an untreated ASR fly ash. The X-ray diffraction detected the enclosed materials on the ASR fly ash primarily contained sulfur associated crystalline complexes. Results indicated the optimal conditions of 30 wt% Thiomer, 30 wt% ASR fly ash and 40 wt% sand reached a compressive strength of 54.9 MPa. For the optimum results in heavy metals leaching, 0.0078 mg/L Pb, 0.0260 mg/L Cr, 0.0007 mg/L Cd, 0.0020 mg/L Cu, 0.1027 mg/L Fe, 0.0046 mg/L Ni and 0.0920 mg/L Zn were leached out, being environmentally safe due to being substantially lower than the Korean standard leaching requirements. The results also showed that Thiomer has superiority over the commonly used Portland cement as a binding material which confirmed its potential usage as an innovative approach to simultaneously synthesize durable concrete and satisfactorily pass strict environmental regulations by heavy metals leaching. © 2017 Elsevier Ltd